Antibacterial Activity Test of 96% Ethanol Extract of Red Ginger (Zingiber officinale var. rubrum) Against the Growth of StreptococcusPneumoniae Bacteria - Harry Nugraha Bachtiar; Irna Diyana Kartika Kamaluddin; Iin Widya Ningsi; Adriani; Dwi Anggita (Jurnal FARMASIMED (JFM), 2025)
Abstract Background: Pneumonia is an infectious disease with a high global prevalence that contributes significantly to mortality in children and adults. Red ginger (Zingiber officinale var. rubrum), a traditional Indonesian medicinal plant, has been identified as having antibacterial, antioxidant, and anti-inflammatory properties. Some of its natural constituents, such as flavonoids, have shown antimicrobial activity with a low toxicity profile. Therefore, the phytochemical content in red ginger is assumed to be able to combat Streptococcus pneumoniae bacteria, which is one of the main etiologies of Pneumonia. Objective: Evaluating the potential of 96% ethanol extract of red ginger (Zingiber officinale var. rubrum) as an antimicrobial agent in inhibiting the growth of Streptococcus pneumoniae bacteria. Method: This study applied a true experimental approach with a post-test design to evaluate the effectiveness of 96% ethanol extract of red ginger (Zingiber officinale var. rubrum) as an agent that inhibits the growth of Streptococcus pneumoniae bacteria. The method used was the disc diffusion method (Kirby-Bauer). Results: The study showed that the ethanol extract of red ginger (Zingiber officinale var. rubrum) exhibited antibacterial activity; however, its effectiveness in inhibiting the growth of Streptococcus pneumoniae was not significant.Conclusion: The 96% ethanol extract of red ginger (Zingiber officinale var. rubrum) demonstrated resistance, showing only minimal inhibitory activity against Streptococcus pneumoniae. This condition contrasts with the positive control, chloramphenicol, which produced a significant inhibition zone and was categorized as sensitive. Therefore, the effectiveness of red ginger extract in inhibiting the growth of this bacterium is considerably lower than that of chloramphenicol.